RARS1 inhibits ENO1 ubiquitination and degradation to protect against ferroptosis in hepatocellular carcinoma - Zang, Shouge; Ma, Jvlong; Chen, Lichang; Cui, Di; Yu, Jiangtao (Frontiers in Immunology, 2025)
BackgroundLiver hepatocellular carcinoma (LIHC) is an aggressive malignancy with high recurrence and therapy resistance. Transplant rejection-related genes (ARRGs) have emerged as potential contributors to cancer progression. This study investigates the role of RARS1, a gene involved in protein synthesis, in LIHC progression and its therapeutic potential.MethodsAR-DEGs in LIHC were identified via differential expression and Cox regression analyses, followed by non-negative matrix factorization (NMF) to classify patients into molecular subtypes. Immune microenvironment, immune evasion, and stemness differences were assessed. Multi-omics datasets, including transcriptomic, single-cell, and spatial transcriptomics, were used to evaluate RARS1 expression. Bioinformatics and molecular biology techniques were employed to study RARS1’s role in oncogenic pathways, immune modulation, and ferroptosis, including interaction with ENO1. Drug sensitivity analysis identified potential RARS1-targeting compounds.ResultsThree LIHC subtypes with distinct immune landscapes and prognoses were identified. Cluster 1 exhibited high immune infiltration and poor response to immune checkpoint blockade. RARS1 was significantly overexpressed in LIHC and correlated with poor prognosis. Knockdown of RARS1 inhibited proliferation and migration of LIHC cells and influenced immune cell polarization. Mechanistically, RARS1 regulated the PI3K/AKT/GSK3β pathway and suppressed ferroptosis via ENO1. Drug analysis revealed AH.6809 as a potential inhibitor of RARS1, reducing its oncogenic effects in vitro.ConclusionAR-DEG-based subtyping reveals distinct LIHC immune profiles. RARS1 promotes LIHC progression through oncogenic signaling and immune modulation, serving as a promising prognostic biomarker and therapeutic target. Targeting RARS1 with agents like AH.6809 may offer novel treatment strategies for LIHC.